The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1002/j.2161-0045.1999.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Telling a Good Story: Using Narratives in Vocational Rehabilitation With Veterans

Abstract: Because of the high chronicity of work‐related problems in a Veterans Administration Medical Center population, many of the traditional methods of career assessment, counseling, and placement have proven ineffectual. In this article the authors detail the development of an intervention based on narrative or storytelling principles. They describe efforts to introduce this model to patients as well as to relate patients' stories to vocational outcomes. The usefulness of stories as an organizing principle for cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…For example, in a study of 317 veterans, most participants indicated they wanted to learn how to transfer skills they learned in the military to the workplace (Hayden, Ledwith, Dong, & Buzzetta, 2014). In a qualitative study with 14 veterans, Krieshok, Hastings, Ebberwein, Wettersten, and Owen (1999) found that veterans who transitioned to civilian life after deployments encountered several challenges regarding their vocational identities. These challenges included experiencing doubts about their ability to work and readiness to make vocational changes (Krieshok et al, 1999).…”
Section: Career Transitionsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in a study of 317 veterans, most participants indicated they wanted to learn how to transfer skills they learned in the military to the workplace (Hayden, Ledwith, Dong, & Buzzetta, 2014). In a qualitative study with 14 veterans, Krieshok, Hastings, Ebberwein, Wettersten, and Owen (1999) found that veterans who transitioned to civilian life after deployments encountered several challenges regarding their vocational identities. These challenges included experiencing doubts about their ability to work and readiness to make vocational changes (Krieshok et al, 1999).…”
Section: Career Transitionsmentioning
confidence: 99%
“…In a qualitative study with 14 veterans, Krieshok, Hastings, Ebberwein, Wettersten, and Owen (1999) found that veterans who transitioned to civilian life after deployments encountered several challenges regarding their vocational identities. These challenges included experiencing doubts about their ability to work and readiness to make vocational changes (Krieshok et al, 1999). Krieshok et al (1999) suggested that veterans’ telling stories about their past jobs and careers and current goals helped them plan better for their future careers and vocational identities.…”
Section: Career Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, there has been limited research and discussion regarding the relationship between trauma symptoms, career development, and vocational behavior. Extant research has focused on providing career counseling to specific groups of individuals who may have been exposed to traumatic events or who have a high likelihood of being exposed to trauma (Bowen, 1982;Gianakos, 1999;Ibrahim & Herr, 1987;Krieshok, Hastings, Ebberwein, Wettersten, & Owen, 1999;Strauser & Lustig, 2001). However, there has been little empirical-based research that has addressed the relationship between trauma, career development, and vocational behavior.…”
mentioning
confidence: 99%